Moral reform and the desiderata of responses to wrongdoing: the production of a "morally autonomous person freely attached to the good" - Waller, Heath Frederick (Rhodes University, Faculty of Humanities, Department of Philosophy, 2004)
Moral reform is a neglected response to wrongdoing that has been incorrectly portrayed as a practice involving illegitimate treatment of wrongdoers and as totally unsatisfying to those theorists advocating backward-looking practices such as retributive punishment. A clear explanation of the ethical legitimacy and practical necessity of the reformative techniques moral reform involves has been missed, and this paper details the design of moral reform proper in order to fill this gap in punishment theory. The moral reform of an offender is identified as a desideratum of responses to wrongdoing and it is explained what moral reform ought to entail. The claim that moral reform qualifies as the overriding aim of responses to wrongdoing is argued for on the grounds that this practice is capable of achieving all the established ends of responses to wrongdoing. The legitimate desiderata of our practices are identified as those usually selected as the ends of punishment practices, and moral reform must accomplish these if it is to be accepted. Moral reform is shown to realise the goals of punishments as the fortunate effects of what is done to achieve an offender's moral improvement and of what reformees do in taking responsibility for their actions. The suffering involved in moral reform receives particular emphasis since the practice will never satisfy unless it accommodates the widely-held intuition that the offender must suffer sufficiently as a consequence of his wrongdoing. Moral reform is further portrayed as the most meaningful practice for its ability to satisfy the appropriate needs and desires victims have in response to their victimization. A central claim of the thesis is that moral reform best serves the victim, since it most effectively relieves the victim's emotional responses to wrongdoing and is as adept as punishment at the expression of these same emotions. Reformers advocate a constructive response to wrongdoing that benefits all affected parties.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Victims of crimes -- Attitudes; Criminals -- Rehabilitation; Punishment -- Psychological aspects; Social ethics; Punishment